Dialysate Sodium: Rationale for Evolution over Time. Issue 2 (8th January 2017) - Flythe, Jennifer E.; Mc Causland, Finnian R.
Abstract: Oligo‐anuric individuals receiving hemodialysis (HD) are dependent on the dialysis machine to regulate sodium and water balance. Interest in adjusting the dialysate sodium concentration to promote tolerance of the HD procedure dates back to the early years of dialysis therapy. Evolution of dialysis equipment technologies and clinical characteristics of the dialysis population have prompted clinicians to increase the dialysate sodium concentration over time. Higher dialysate sodium concentrations generally promote hemodynamic stabilization and reduce intradialytic symptoms but often do so at the expense of stimulating thirst and promoting volume expansion. The opposite may be true for lower dialysate sodium concentrations. Observational data suggest that the association between dialysate sodium and outcomes may differ by serum sodium levels, supporting the trend toward individualization of the dialysate sodium prescription. However, lack of randomized controlled clinical trial data, along with operational safety concerns related to individualized dialysate sodium prescriptions, have prevented expert consensus regarding the optimal approach to the dialysate sodium prescription.